The platformed money ecosystem: Digital financial platforms, datafication, and reimagining financial well‐being. Issue 3 (14th June 2022) - Ekpo, Akon E.; Drenten, Jenna; Albinsson, Pia A.; Anong, Sophia; Appau, Samuelson; Chatterjee, Lagnajita; Dadzie, Charlene A.; Echelbarger, Margaret; Muldrow, Adrienne; Ross, Spencer M.; Santana, Shelle; Weinberger, Michelle F.
Abstract: Digital financial platforms have become an integral part of consumers' lives–resulting in the datafication of everyday life and potential for uniquely impacting financial well‐being. Extending previous transformative consumer research, we suggest financial well‐being must center the ways digital financial platforms and their resulting data are increasingly enmeshed with financial decision making and consumption. Drawing on a theoretical lens of platformization, we propose the Platformed Money Ecosystem, which accounts for increased embeddedness of digital financial platforms within consumers' lives and the subtlety of how everyday life is transformed into data: producing data at the micro‐level, monetizing data at the meso‐level, and regulating data at the macro‐level. In conceptualizing the Platformed Money Ecosystem, we identify three data‐informed considerations for scholars and policymakers to reimagine financial well‐being: protecting consumer data, limiting data biases, and supporting data literacy.